EFEKTIVITAS VAKSIN POLIVALEN UNTUK PENGENDALIAN VIBRIOSIS PADA KERAPU TIKUS (Cromileptes altivelis) - Kamiso Handoyo Nitimulyo; Alim Isnansetyo; Triyanto Triyanto; Muhammad Murdjani; Lili Sholichah (Jurnal Perikanan Universitas Gadjah Mada, 2005)
The objective of this research was to know the effectiveness of polyvalen  Vibrio vaccine to control vibriosis in humpback grouper (Cromileptes altivelis). The effectiveness of vaccine was evaluated by the survival rate (SR), relative percent survival (RPS), mean time to death (MTD) as well as growth rate of vaccinated fish. This research consisted of 4 treatments (control, injection, immersion, and oral vaccinations) in quadruplicates. Injection  vaccination was conducted by intraperitoneal injection of polyvalen vaccine at 107 cells/fish. Immersion vaccination was done by immersing the fishes at 107 cells/ml for 30 minutes. Oral administration of vaccine was also carried out  at 107 cells/fish. One week after the first vaccination, second vaccination (booster) was carried out at the same dosage and by the same administration. One week after the second vaccination, fishes were challenged with 3.16x104 cells/fish of Vibrio ordalii 3J by intraperitoneal injection, and reared for 20 days post infection. Results indicated that polyvalen Vibrio vaccine increased SR (P<0.01) up to 100%. Vaccination was also able to delay MTD of fishes. However, the vaccination was not influence the growth rate of fish.